Tinjauan Pustaka Penghitungan Jumlah Pohon Pada Foto Dan Beberapa Kendala Yang Perlu Diperhatikan - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1994)
ABSTRACT Number of trees in a forest can be counted on serial photograph based on their visible crowns. It is easier, quicker and cheaper compared to terrestrial direct counting, but less accurate dua to many factors. The factors are structure, composition, age and size of stand forest, quality and specification of the photograph. Ground relief should be studied intensively before counting to increase accuracy. Sample plot should be made at scale at each point to control displacement.